Pementasan Tari Mongah dalam Upacara Pangwangan di Desa Bunutin, Kecamatan Kintamani, Bangli - Ayu Narisma, Ni Kadek; Sama, Nyoman (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p10, 2018)
Bunutin village is one of the Bali Aga villages located in Kintamani Subdistrict, Bangli District, which has art in the form of sacred dance and still maintained or preserved by society. The art is known by the people of Bunutin Village with the name of Mongah Dance. Mongah Dance staged every two years at the time of the Pangwangan Ceremony, precisely on sasih kasa according to Balinese calendar calculations. Pangwangan ceremony is a ritual performed during the post-harvest period, aims to neutralize the negative influences or outbreaks of diseases, disasters and pests that attack the environment. This is done by performing a dance-shaped art called Mongah Dance. The formulation of the problem in this research include (1) How to perform Mongah Dance in Pangwangan Ceremony in Bunutin Village (2) How the function and meaning of Mongah Dance in Pangwangan Ceremony. This research is intended to describe the Dance of Mongah Dance in the procession of Pangwangan Ceremony, and to know the function and meaning of the Dance of Mongah Dance in Pangwangan Ceremony in Bunutin Village related to the pattern of agriculture. The theory used in this research is the theory of Robert K. Merton about the real function (manifest) and the hidden function (latent) and interpretive theory of Clifford Geertz. The method used is qualitative research method. Data collection techniques include observation, interview and literature study. Data analysis used qualitative descriptive analysis. The results revealed that Mongah Dance staged at the procession of Pangwangan Ceremony at Pura Bale Agung. At the time of dance performances Mongah dancers are sekaa teruna influenced by the element of trance. Mongah Dance costumes utilize many plants that exist in nature. In the execution of the Dance of Mongah Dance in Pangwangan Ceremony there are manifest and latent functions. The first function is Mongah Dance is the most important element in the implementation of Pangwangan Ceremony, Mongah Dance functioned to keep people away from negative elements, and Mongah Dance can strengthen solidarity among the citizens. In addition to the function as for the meaning contained in the staging of Mongah Dance in Pangwangan Ceremony is the meaning to ask for salvation, meaning as a symbol of harmonization, and the meaning of kinship.